Quality of life among newly diagnosed lung cancer patients in Iceland: The role of resilience and social support - Harpa Sóley Snorradóttir 1971- (2018)
Lung cancer is one of the most commonly diagnosed cancer world-wide and leading causes of cancer deaths in the developed world. A diagnosis of lung cancer is a severely stressful event illustrated by the dramatic increase in psychiatric disorders in newly diagnosed population. Nevertheless, there is a great variability in how patients respond to the diagnosis of cancer. This may be partly explained by the nature and quality of support that patients have, individuals coping skills and resilience. The purpose of this study was to assess the quality of life of patients with newly diagnosed lung cancer and the potential role of social support and resilience on their quality of life. The study was a prospective cohort study at the pulmonary department at Landspitali, University Hospital in Iceland. The study cohort consisted of 35 patients referred for a diagnostic work up due to suspected lung cancer and followed until the lung cancer diagnosis was established. Social support was assessed with Berkman-Syme Social Network Index (SNI) and resilience was measured using Connor Davidson resilience scale (CD-RISC-10) at the diagnostic work up. Items from the Functional Assessment for Cancer Therapy-Lung Cancer (FACT-L) were used to measure quality of life after lung cancer diagnosis. The mean age of participants was 71 years; women representing half of the population. Younger patients (60-69 years) reported higher social support (p=0.02) compare to older patients (70 years or older), but no other statistically significant association was found between background/clinical characteristic and social support and resilience. Women reported better functional wellbeing (FWB) compared to men (p=0.05). Higher levels of social support prior to cancer diagnosis was associated with better social/family wellbeing (SWB) following cancer diagnosis (p=0.02). No statistically significant association was found between resilience and quality of life. Yet, both emotional well-being (EWB) and general well-being (FACT-G) were marginally ...